The effect of COVID-19 pandemic on emotional wellbeing of education instructors: A perspective of Kenya’s private schools - Busolo, Hillary; Jerop, Caren; Omulando, Carolyne (Journal of Educational Management and Instruction (JEMIN), 2023)
The COVID-19 pandemic phenomenon generated inordinate strain and experiences across a wide range of sectors in Kenya, with the education segment introduced to its own set of unique challenges. Some instructors in private learning institutions joined the job seeking market once again as several schools indefinitely closed down. This often-needed reskilling and turned out to be frustrating as the job opportunities kept shrinking rapidly. This study looked at the effect of COVID-19 pandemic education disruption on emotional wellbeing of education instructors, with a focus on private schools’ teachers in Kenya. Data was collected from 367 respondents who completed a closed ended questionnaire and quantitative analysis was undertaken. The results revealed that there is a significant effect of COVID-19 pandemic education disruption on private school teachers’ emotional wellbeing. The prediction equation based on the unstandardized coefficients was statistically significant, F 1,365 = 46.035, p < 0.001 and accounted for approximately 11.2% of the variance of emotional wellbeing (R2 = 0.112, Adjusted R2 = 0.110). Therefore, hypothesis stated as COVID-19 pandemic education disruption has no significant effect on Kenyan private school teachers’ emotional wellbeing was not supported. The moderating effect of emotional and physical support did not significantly account for more variance with R2 Change = .009, p > .024. The findings supported the hypothesis that emotional and physical support does not moderate the effect of Covid-19 pandemic education disruption on Kenya private school teachers’ emotional wellbeing.